Indian Spices and Condiments as Natural Healers - H K Bakhru; BAKHRU (H K) (Mumbai Jaico Publishing House, 2001)
Spices and condiments are important forms of natural foods. However, besides having culinary uses, they are also utilized for natural healing purposes. Perfumes, essential oils, edible restoratives and other components of spices provide significant benefits to human beings. In Indian Spices and Condiments as Natural Healers, Dr. Bakhru describes the medicinal virtues of a variety of spices and condiments. The author's easy-to-understand and detailed descriptions expose readers to the distinctive qualities of specific spices, and their ability to treat common ailments like headaches, colds, migraines and coughs. The information in this book can assist readers in solving common health problems. In addition, readers will learn how to use spices and condiments as essential ingredients of a well-balanced natural diet.
Keywords: Indian Spices; Medical Plants